2020
DOI: 10.1111/imj.15091
|View full text |Cite
|
Sign up to set email alerts
|

Aeromedical retrieval diagnostic trends during a period of Coronavirus 2019 lockdown

Abstract: Background Little is known on the trends of aeromedical retrieval during social isolation. Objectives To compare the pre, lockdown, and post‐lockdown aeromedical retrieval (AR) patient characteristics during a period of Coronavirus 2019 (COVID‐19) social isolation. Methods An observational study with retrospective data collection, consisting of AR between 26 January and 23 June 2020. Results There were 16981 ARs co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Fortunately the RFDS experienced substantial reduction in acute coronary syndrome (ACS) transfers during the restriction. This demand rebounded soon afterward 1 . Similarly, the Feedback Intervention and Treatment Times in ST‐Elevation Myocardial Infarction (FITT‐STEMI) study observed a worrying 12.6% decrease in STEMI presentations and interhospital transfers during the pandemic peak in regional Germany 7 .…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Fortunately the RFDS experienced substantial reduction in acute coronary syndrome (ACS) transfers during the restriction. This demand rebounded soon afterward 1 . Similarly, the Feedback Intervention and Treatment Times in ST‐Elevation Myocardial Infarction (FITT‐STEMI) study observed a worrying 12.6% decrease in STEMI presentations and interhospital transfers during the pandemic peak in regional Germany 7 .…”
mentioning
confidence: 97%
“…In this issue of the Internal Medicine Journal , Gardiner et al 1 . offer valuable lessons from their considered and comprehensive analyses of aeromedical retrieval patterns for the whole Royal Flying Doctor Service (RFDS) network during the 7 weeks before, during and after, Australia's COVID‐19 restrictions imposed between 16 March and 4 May 2020.…”
mentioning
confidence: 99%
See 3 more Smart Citations